A Proposed Learning Design: Application of Differential and Integral Concepts By Modeling the Heating Process of Glucose Solution - Deklin Frantius; Liliasari Liliasari; Asep Bayu Dani Nandiyanto (Publikasi Indonesia, 2025)
The concepts of differential and integral are important topics in chemistry mathematics courses. Based on the number of subtopics, differential and integral concepts are covered on average more than 40% in chemistry mathematics books. Several previous studies reported findings that differential and integral concepts are still difficult for students to understand. This research aims to evaluate the previous lecture program and propose an alternative learning design to help students more easily understand those concepts. In this study, we developed a practicum by adopting Plomp’s model, which were collecting, designing, trying, and revising the product. The practicum design was developed for heating process of glucose solution. Those chemicals were chosen because the materials obtained are relatively easy, cheap, and safe, so it is very possible to practice it in the laboratory. We used Maple to model the heating process phenomenon. The results show that the differential and integral concepts can be applied to model the heating process of glucose solution by using Maple. This research is limited to simulations. Therefore, the suggestion for further research is to conduct field trials to determine the impact of implementing learning design in increasing students' understanding of differential and integral concepts.